(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The present investigation is aimed to evaluate anti-arthritic activity of the ethanol extract of root of Momordica charantia (EEMR) by using Freund’s complete adjuvant (FCA) induced arthritis model which is a extensively used model for in-vivo study of anti-arthritic activity. Arthritis assessment was carried out on basis of parameters i.e. arthritis score, joint diameter and paw volume. The standard drug was diclofenac sodium. The findings of present study showed that EEMR in dose of 400 mg/kg produced more significant reduction in arthritis score, joint diameter and paw volume as compare to 200 mg/kg. On the basis of results, it can be concluded that EEMR showed significant anti-arthritic activity. It may be due to presence of phytocompounds such as flavonoids, alkaloids, tannins etc.